A systematic review and meta-analysis investigating head trauma in boxing - Donnelly, R. R.; Ugbolue, U. C.; Gao, Y.; Gu, Y.; Dutheil, F.; Baker, J. S. (Clinical Journal of Sport Medicine, 2023)
Objectives: Although physical trauma has been reported in boxing since its inception, boxing still appeals to athletes and spectators. This systematic review and meta-analysis assess both acute and chronic neurological and neuropsychological effects that boxing has on the brain. Further assessments in terms of comparisons of the concussion ratio in boxing to other combat sports, as well as the efficiency of wearing headguards, are also performed.